Capital Structure Evaluation Based Company Sizes And Profitability - Aprih Santoso; Sri Yuni Widowati; Emaya Kurniawati (Jurnal Akuntansi dan Pajak, 2020)
The purpose of this study is to evaluate the effect of : (1) Firm Size on Profitability (ROA). (2) Firm Size on Capital Structure (DER). (3) Profitability (ROA) on Capital Structure (DER) in the Manufacturing Sector Automotive Companies and Components on the IDX. The data used are secondary data using a sample of 13 automotive sector manufacturing companies and components listed on the Indonesia Stock Exchange in 2016-2018. Sampling was done using a sensus method. This research uses a quantitative approach and the analysis technique used is multiple linear regression analysis (path analysis. The results of this study are: (1) FirmSize significantly has a positive effect on profitability (ROA). (2) Firm Size significantly has a positive effect on capital structure (DER). (3) Profitability (ROA) significantly has a positive effect on capital structure (DER).